Environmental concerns of Malaysian and foreign residents of Langkawi towards the degradation of mangroves in Kilim Karst Geoforest Park Langkawi - Fong, May Yin (2019)
Kilim Karst Geoforest Park Langkawi (KKGP) is one of the main tourism island, Langkawi’s natural coastal protector as well as the perfect nursery for marine creatures. However, studies have found that the mangrove cover in KKGP Langkawi has degraded over the years. Conservation steps need to be taken and one of the ways is to increase the environmental concerns of the residents to encourage environmental responsibly behavior. The first objective of this study is to predict the relationship between environmental concerns, awareness of impact and willingness to take action in Langkawi residents. The second objective is to compare the environmental concerns, awareness of impact and willingness to take action between Malaysian and foreign Langkawi residents. Results shows that environmental concern was found to be relatable and have high correlation with awareness and willingness to take action. Moreover, results indicated that KKGP was well known among the residents and were visited by residents quite frequently. Therefore, both Malaysian and foreign residents were similarly concern and aware of the impact towards the degradation of mangrove. However, in terms of willingness to take action, Malaysian residents are more likely, compared to foreign residents due to global cultures and attitude differences. In general, all residents are environmentally concerned on the degradation of mangroves in KKGP Langkawi.